TINGKAT KECEMASAN REMAJA PUTRI DALAM MENGHADAPI PREMENSTRUAL SYNDROME DI SMP 2 SOOKO MOJOKERTO - Indatul Laili, Siti; Lestari Dewi, Lendri (JURNAL KEPERAWATAN BINA SEHAT, 2014)
ABSTRACTSyndrome pre menstruation is a series of changing body ang psychology, wich is started in 2-14 days before menstrual then abate almost in the moment of getting menstruation. Generally, kind of psychology’s symptoms, which is gotten by adolescent girls in the moment of pre menstruation, is worrying of facing syndrome pre menstruation. The purpose of this research is to know the level of worried in adolescent girls facing syndrome pre menstruation in SMPN 2 Sooko Mojokerto. Design of this research is Descriptive. The population is 117 adolescent girls in SMPN 2 Sooko Mojokerto and the sample of this research is 117 adolescent girls taken by total sampling. Data is collected by questionnaire that is provided in table’s distribution frequency form. The result of this research shows that ahalf of responden get middle level worried in facing pre menstruation syndrome is 71 respondents . That woried is influenced by some factors, such as knowledge, education,age, experience in the past and sex, in addition , adolescent girls should more add the knowledge about pre menstruation syndrome in order worried is avoided, by looking for the information as like reading science books, reading form electronic media and asking the expert in healthy.Keywords: Worried level, adolescent girls, syndrome pre menstruation